A novel methodology for the design of diffuser-augmented hydrokinetic rotors. (July 2023) - Rezek, Thiago J.; Camacho, Ramiro G.R.; Manzanares-Filho, Nelson
Abstract: Shrouded wind and hydrokinetic turbines are being widely studied nowadays. Although actuator disk studies have concluded that the addition of a diffuser around a rotor can improve the Power Coefficient, not many designs have realized those benefits when compared to standard high performance bare turbines, as shown by Nunes et al. (2020) [1]. One reason for low power coefficient on several designs is massive flow separation on the hub surface due to high adverse pressure gradient inside the diffuser, resulting on low mass flow capture and, hence, poor performance. This work presents a novel design methodology for shrouded rotors, which takes into consideration the influence of the entire linear cascade on each annular section. Also, the blade root is left unloaded to guarantee that no boundary layer separation occurs on the hub surface by allowing a layer of energized fluid to bypass the rotor. A turbine modeled by this method has been numerically studied and is shown herein to deliver a peak power coefficient of 0.415 normalized by the diffuser's largest cross sectional area. Graphical abstract: Image 1